Analysis and optimization of small modular reactors contribution to the power production of Greece - Kaissas Ioannis M.; Nikolaidis Nikolaos I. (Nuclear Technology and Radiation Protection)
Following the global trend for carbon-free energy production, Greece shut down most of its coal power plants and installed solar and wind systems for electricity production. Due to the time variations in the energy production of these systems, a complementary power source is needed, with the ability to change its output on demand. Small modular reactors combine zero-carbon emissions with the ability to vary the power production on demand. The objective of this study is to examine the energetic competitiveness of five appropriately selected small modular reactors compared to the total power production of coal power plants in Greece. The daily and monthly distribution of generated energy of the previous year (2023) is analyzed to demonstrate the potential operation of small modular reactors in Greece's electrical grid. The outcome addresses whether deploying a small modular reactor is energetically beneficial for Greece and indicates the number of modules required or how many small modular reactors, in combination with renewable sources, can meet the demand. The annual coal power plant production of Greece of 4.5 TWh can be substituted with one multi-module small modular reactor or a combination of them, appropriately located.